Cd branding studies in a homologous Robertsonian 13;13 translocation. Issue 4 (August 1982) - Romain, D R; Columbano-Green, L; Sullivan, J; Smythe, R H; Gebbie, O; Parfitt, R; Chapman, C
Abstract : A phenotypically normal female with a history of two miscarriages was found to have the karyotype 45, XX, t(13p:13p). C banding showed the translocation to have two regions of centromeric constitutive heterochromatin, silver staining showed an active NOR in 60% of the cells screened, and Cd banding studies showed a single Cd band with absence of the Cd band at the suppressed centromere.